Special honours for UPM academics - The Star, Kang Soon Chen (2012)
EARLIER this month, International Trade and Industry Minister Datuk Seri Mustapa Mohamed announced that the country's export of halal products had gone up from RM23.1bil in 2010 to RM35.4bil as of last year.